Parallel screening for ALK, MET and ROS1 alterations in non-small cell lung cancer with implications for daily routine testing. Issue 2 (February 2015) - Jurmeister, Philipp; Lenze, Dido; Berg, Erika; Mende, Stefanie; Schäper, Frank; Kellner, Udo; Herbst, Hermann; Sers, Christine; Budczies, Jan; Dietel, Manfred; Hummel, Michael; von Laffert, Maximilian
Highlights This is the first report on parallel FISH and IHC screening for ALK, MET and ROS1. Concordant results for ALK IHC and ALK FISH were seen in all cases. MET FISH and IHC showed discordant results in 10.0% of cases. MET overexpression can occur in ALK rearranged tumors. Besides rearrangements, ROS1 amplifications can also occur in NSCLCs.